Elaboration of Vienna-type Sausage from Jumbo squid pulp (Dosidicus gigas) - Gutierrez Huayra, Richard Smith (Ingeniería Química y Desarrollo, 2026)
The jumbo squid (Dosidicus gigas) is an abundant and nutritious marine resource with the potential to diversify the food industry through value-added products. The study aimed to evaluate the feasibility of producing a vienna-type sausage using jumbo squid pulp, optimizing its formulation and sensory acceptability. Three formulations with 5%, 8%, and 10% starch were developed. The process included conditioning, leaching, grinding, homogenization, stuffing, blanching, cooling, and refrigeration. Acceptability was evaluated by a panel of 30 untrained judges using the Friedman test. Chemical-nutritional and microbiological analyses were conducted to determine the product’s nutritional value and safety. The formulation with 8% starch received the highest acceptance in flavor, appearance, and texture. The optimal processing parameters were: emulsification at 10 °C, cooking at 70 °C for 23 min, and cooling at 2–4 °C for 5 min, resulting in energy savings compared to other formulations. Per 100 g, the product contained 17.4 g protein, 1.2 g fat, 1.3 g carbohydrates, and 125 Kcal, with lower fat and calorie content than the control sausage. Microbiological analyses confirmed its safety, showing low aerobic counts and absence of pathogens. The production of Vienna-type sausage based on jumbo squid pulp proved viable, offering nutritional, sensory, and sanitary, advantages for the diversification of fishery products.